Reog Ponorogo: A case study of structure in kumpulan Sri Wahyuni in Batu Pahat / Nina Nashrah Abdul Jalal - Nina Nashrah , Abdul Jalal (2019)
The research studies on Reog Ponoroogo by Kumpulan Sri Wahyuni in Batu Pahat Johor. The aim of the study is to analyse the factors that contribute in the changes of the structure due to the process of acculturation on Reog Ponorogo by Kumpulan Sri Wahyuni and to study on its structures of Reog Ponorogo that is caused by the process of acculturation. The study is based on the theories of acculturation and has adopted a research design of qualitative research that uses the method of collecting data from reading materials and from the observations and interviews that were collected from Kumpulan Sri Wahyuni. The finding of this study reveals that the structures of Reog Ponorogo by Kumpulan Sri Wahyuni did undergo changes that are caused by the process of acculturation. The changes can be seen in the elements that have been discarded by the organization in order to conform to the norms of the society which involves the culture and the rules of Malaysia. The findings of the study should enable the readers and future researcher to have a better understanding on the performance of Reog Ponorogo and is expected to inspire the next researcher to conduct a deeper investigation on this performance from any elements in the structures and to inspire the next researcher to investigate the different styles of structures practiced by the practitioners of this performance either in Batu Pahat or in Selangor.